2004
DOI: 10.1016/j.joms.2004.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Modeling facial movement: II. A dynamic analysis of differences caused by orthognathic surgery

Abstract: Purpose-The purpose of this study was to determine the facial movement characteristics of patients who underwent orthognathic surgery. The specific aims were to determine the presurgery versus postsurgery differences in facial movements; to determine whether the presurgery facial movements were similar among patients with different dentofacial deformities; and to determine whether patients have a more similar post-than presurgery dentofacial morphology and soft tissue movement. The hypothesis was that there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 16 publications
5
53
1
1
Order By: Relevance
“…We suggest a new study with a larger sample to confirm this trend. In addition, the literature does not show a relationship between DFD and expression wrinkles; however, researches have shown that DFD individuals had difficulties to perform facial mimics in the preoperative period 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…We suggest a new study with a larger sample to confirm this trend. In addition, the literature does not show a relationship between DFD and expression wrinkles; however, researches have shown that DFD individuals had difficulties to perform facial mimics in the preoperative period 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Using of this method is widespread in the smile position rather than the rest position. 27 Schabel et al 28 reported that digital videography method gives us a lot of information for assessing the dynamic properties of smile, but the standard digital photography method is still sufficient for evaluation of smiles after treatment.…”
Section: Dynamic Recordsmentioning
confidence: 99%
“…This morphology is never static, but it continuously acts and reacts to environmental and internal stimuli. The face plays a major role in social communication and interaction (Hennessy et al, 2005;Johnson and Sandy, 2003;Matoula and Pancherz, 2006;Nooreyazdan et al, 2004;Tarantili et al, 2005), and it carries information that allows the identification of a single person (DeCarlo et al, 1998;Fraser et al, 2003;Shi et al, 2006).Functional impairments in facial expression may be caused by central nervous system diseases (Parkinson disease), facial nerve paralysis, dentofacial deformities and scars, congenital anomalies like cleft lip (Linstrom, 2002;Linstrom et al, 2002;Mishima et al, 2004;Nooreyazdan et al, 2004;Tarantili et al, 2005;Trotman et al, 1998a; Wachtmann et al, 2001), and may provoke serious alterations in the quality of life of the patients. Additionally, modifications in facial motion had been reported in patients affected by several psychiatric disorders (Mergl et al, 2005).…”
mentioning
confidence: 99%
“…In the past, static (photographic) and dynamic (cinematographic) two-dimensional systems had been devised and applied in several clinical contests (Linstrom, 2002;Linstrom et al, 2002;Tarantili et al, 2005; Wachtmann et al, 2001). Unfortunately, facial motion is a complex activity that develops in all three spatial planes; two-dimensional recordings can significantly underestimate facial movements (Frey et al, 1999;Gross et al, 1996;Nooreyazdan et al, 2004).Currently, various three-dimensional motion analyzers allow a non-invasive quantitative assessment of soft tissue facial movements without interfering with the subject, and details about instruments, measurement protocols and data analysis have been reported (Frey et al, 1999;Giovanoli et al, 2003;Johnston et al, 2003;Mergl et al, 2005;Mishima et al, 2004;Nooreyazdan et al, 2004;Weeden et al, 2001).Previous investigations developed standardized sequences of facial animations, but only symmetric movements had been studied so far. In contrast, asymmetric motions could allow a better assessment of unilateral facial palsy, for instance after facial nerve lesion.…”
mentioning
confidence: 99%
See 1 more Smart Citation